1977
DOI: 10.1037/0022-0663.69.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Peer-tutoring outcomes as influenced by the equity and type of role assignment.

Abstract: This field experiment, with an initial sample of 178 undergraduate classmates engaged in same-age peer tutoring, was conducted to test a theoretical model that attached greater desirability (a) to be the tutor than tutee and (b) to be in an equitable (status-congruent) rather than inequitable relationship. Same-sex pairs were formed such that the tutor had relatively greater (the equity condition), equal, or lower pretest competency than the tutee. Partners in half the'pairs exchanged roles for the second of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Students who take on both roles in the tutoring dyad may learn more than those who take on just one or the other (Rosen et al, 1978). Reciprocal and classwide peer-tutoring programs, in which students switch between the roles of tutor and tutee, consistently produce good results, although reciprocal peer-tutoring programs often use rewards, which may also contribute to their success.…”
Section: Implications Of Research Findings Regarding Outcomes For Peementioning
confidence: 90%
See 1 more Smart Citation
“…Students who take on both roles in the tutoring dyad may learn more than those who take on just one or the other (Rosen et al, 1978). Reciprocal and classwide peer-tutoring programs, in which students switch between the roles of tutor and tutee, consistently produce good results, although reciprocal peer-tutoring programs often use rewards, which may also contribute to their success.…”
Section: Implications Of Research Findings Regarding Outcomes For Peementioning
confidence: 90%
“…Some students who receive help from peers may feel deficient, angry, or shamed (Rosen et al, 1978;Schofield, 1980), especially when the helper is not performing a formal role and when the situation may reinforce racial stereotypes regarding academic competence (Schofield, 1980). However, this effect is likely minimal when tutoring is a formal, accepted learning strategy for the class, or when reciprocal peer tutoring is used, enabling the helped to become the helper (cf.…”
Section: Role Theorymentioning
confidence: 98%
“…Medway & Lowe (1980) found that students in a cross-age tutoring study attributed their success in learning to their tutoring partner and to their own efforts, rather than to their ability. With older learners, junior high and above, it has generally been found that predicted satisfaction and achievement as well as actual achievement are greater for the tutor than for the student (Rosen et al, 1977;Rosen et al, 1978;Bargh & Schul, 1980).…”
Section: Classroom Processesmentioning
confidence: 99%
“…The tutor role itself is of importance to students' experience of peer learning. Participant satisfaction, perceptions of good performance and actual performance were directly dependent on becoming a tutor and entering an equitable relationship in a psychological assessment of student perceptions of peer learning arrangements conducted by Rosen et al 11 In their test of undergraduate general and specific competence, measured performance was contrasted in students who read material only, read with the expectation of having to teach it to a peer and read the material and taught it to a peer 11 . The tutors learned more than the tutees in this experiment.…”
Section: Introductionmentioning
confidence: 99%